Neural Correlates of Public Apology Effectiveness - Kim, Hoh; Kralik, Jerald D.; Yun, Kyongsik; Chung, Yong-an; Jeong, Jaeseung (Frontiers in Human Neuroscience, 2019)
Apologizing is an effective interpersonal conflict resolution strategy, but whether organizations should issue public apologies after crises has been less clear. Recently it was shown that public apologies are effective, especially when they provide a comprehensive account of what happened and clear actions taken by the company to address the problems. Intriguingly, public apologies may be most effective when the crisis source resides within the organization itself, suggesting that the company has control over it. In the current study we first attempted to replicate this behavioral finding by presenting participants with multiple crisis scenarios (e.g., ignition failures in a new car model) followed by one of two written apologies: one stating that the crisis source was internal to and controllable by the organization, and the other that it was external and uncontrollable. Replicating the previous study, we found that the internal-controllable public apology was most effective. We then examined the neural basis of this public apology assessment and found that the ventrolateral prefrontal cortex appears to mediate the believability of organizational control, and the precuneus uses the information for the apology assessment. Examination of complex social interactions, such as the public’s response to corporate crises, help elucidate high-level brain function.